A Stimulatory Role for Cytokinin in the Arbuscular Mycorrhizal Symbiosis of Pea - Goh, Dane M.; Cosme, Marco; Kisiala, Anna B.; Mulholland, Samantha; Said, Zakaria M. F.; Spíchal, Lukáš; Emery, R. J. Neil; Declerck, Stéphane; Guinel, Frédérique C. (Frontiers in Plant Science, 2019)
The arbuscular mycorrhizal (AM) symbiosis between terrestrial plants and AM fungi is regulated by plant hormones. For most of these, a role has been clearly assigned in this mutualistic interaction; however, there are still contradictory reports for cytokinin (CK). Here, pea plants, the wild type (WT) cv. Sparkle and its mutant E151 (Pssym15), were inoculated with the AM fungus Rhizophagus irregularis. E151 has previously been characterized as possessing high CK levels in non-mycorrhizal (myc-) roots and exhibiting high number of fungal structures in mycorrhizal (myc+) roots. Myc- and myc+ plants were treated 7, 9, and 11 days after inoculation (DAI) with synthetic compounds known to alter CK status. WT plants were treated with a synthetic CK [6-benzylaminopurine (BAP)] or the CK degradation inhibitor INCYDE, whereas E151 plants were treated with the CK receptor antagonist PI-55. At 13 DAI, plant CK content was analyzed by mass spectrometry. The effects of the synthetic compounds on AM colonization were assessed at 28 (WT) or 35 (E151) DAI via a modified magnified intersections method. The only noticeable difference seen between myc- and myc+ plants in terms of CK content was in the levels of nucleotides (NTs). Whereas WT plants responded to fungi by lowering their NT levels, E151 plants did not. Since NTs are thought to be converted into active CK forms, this result suggests that active CKs were synthesized more effectively in WT than in E151. In general, myc+ and myc- WT plants responded similarly to INCYDE by lowering significantly their NT levels and increasing slightly their active CK levels; these responses were less obvious in BAP-treated WT plants. In contrast, the response of E151 plants to PI-55 depended on the plant mycorrhizal status. Whereas treated myc- plants exhibited high NT and low active CK levels, treated myc+ plants displayed low levels of both NTs and active CKs. Moreover, treated WT plants were more colonized than treated E151 plants. We concluded that CKs have a stimulatory role in AM colonization because increased active CK levels were paralleled with increased AM colonization while decreased CK levels corresponded to reduced AM colonization.